Дорожній травматизм та регіональна система травматологічної допомоги: медичний та територіальний аспекти (на прикладі Сумської області) = Road traffic injuries and regional system of trauma care: medical and territorial aspects (case study of Sumy region) - Shyschuk, Volodymyr; Kornus, Anatolii; Kornus, Olesia; Dominas, Valentyna (Journal of Education, Health and Sport, 2016)
Shyschuk Volodymyr, Kornus Anatolii, Kornus Olesia, Dominas Valentyna. Дорожній травматизм та регіональна система травматологічної допомоги: медичний та територіальний аспекти (на прикладі Сумської області) = Road traffic injuries and regional system of trauma care: medical and territorial aspects (case study of Sumy region). Journal of Education, Health and Sport. 2016;6(9):460-470. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154277 http://ojs.ukw.edu.pl/index.php/johs/article/view/3856 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. УДК 616-001.3 : 656.06 (477.52) ДОРОЖНІЙ ТРАВМАТИЗМ ТА РЕГІОНАЛЬНА СИСТЕМА ТРАВМАТОЛОГІЧНОЇ ДОПОМОГИ: МЕДИЧНИЙ ТА ТЕРИТОРІАЛЬНИЙ АСПЕКТИ (НА ПРИКЛАДІ СУМСЬКОЇ ОБЛАСТІ) ROAD TRAFFIC INJURIES AND REGIONAL SYSTEM OF TRAUMA CARE: MEDICAL AND TERRITORIAL ASPECTS (CASE STUDY OF SUMY REGION) Володимир Шищук 1, Анатолій Корнус 2, Олеся Корнус 2, Валентина Домінас 3 Volodymyr Shyschuk, Anatolii Kornus, Olesia Kornus, Valentyna Dominas 1 Сумський державний університет, медичний інститут, м. Суми 2 Сумський державний педагогічний університет, м. Суми 3 Сумська міська клінічна лікарня №1, м. Суми 1 Medical Institute of Sumy State University, Ukraine, Department of Orthopedics and Traumatology, Sanatorna Street 31, Sumy, 40018 2 Sumy State Pedagogical University named after A.S. Makarenko, Ukraine, Department of General and Regional Geography, Romens’ka Street 87, Sumy, 40002 3 Sumy City Clinical Hospital №1, Ukraine, 20 Rokiv Peremohy Street 13, Sumy, 40021 e-mail: a_kornus@ukr.net Summary In the article the medical and territorial peculiarities of the prevalence of road traffic accidents in the Sumy region were investigated. The dynamics of accidents on the roads and streets of the region and their implications were also considered, as well as the reasons that affect the number and severity of road accidents. The structure of accident by victims and perpetrators by type was given. We characterized the territorial peculiarities of road traffic accidents and the groups of administrative regions by number of road crashes and level of injury trauma care were made. Recommendations to reduce the impact of road accidents and to improve the organization of medical care to the victims are proposed in the article. Keywords: traffic accident, road traffic injuries, road crashes, trauma hospital beds, medical care, Sumy region. Анотація У статті досліджено медичні та територіальні особливості поширеності дорожньо-транспортного травматизму у Сумській області. Проаналізовано динаміку аварій на дорогах і вулицях регіону та їх наслідки. Визначено причини, що впливають на кількість і тяжкість дорожньо-транспортних пригод (ДТП). Розглянуто структуру ДТП з постраждалими за типами та винуватцями. Охарактеризовано територіальні особливості дорожньо-транспортного травматизму та виділено групи адміністративних районів за величиною травматизму та рівнем надання травматологічної допомоги. Запропоновано рекомендації щодо зменшення наслідків дорожньо-транспортних пригод та покращення організації медичної допомоги постраждалим. Ключові слова: дорожньо-транспортна пригода, дорожньо-транспортний травматизм, аварійність, травматологічні ліжка, медична допомога, Сумська область. Резюме В статье исследованы медицинские и территориальные особенности распространенности дорожно-транспортного травматизма в Сумской области. Проанализирована динамика аварий на дорогах и улицах региона и их последствия. Определены причины, влияющие на количество и тяжесть дорожно-транспортных происшествий (ДТП). Рассмотрена структура ДТП с пострадавшими по типам и виновникам. Охарактеризованы территориальные особенности дорожно-транспортного травматизма и выделены группы административных районов по величине травматизма и уровню оказания травматологической помощи. Предложены рекомендации по уменьшению последствий дорожно-транспортных происшествий и улучшению организации медицинской помощи пострадавшим. Ключевые слова: дорожно-транспортное происшествие, дорожно-транспортный травматизм, аварийность, травматологические кровати, медицинская помощь, Сумская область.